2017
DOI: 10.1155/2017/5750897
|View full text |Cite
|
Sign up to set email alerts
|

Small Interfering RNA Targeting Mitochondrial Calcium Uniporter Improves Cardiomyocyte Cell Viability in Hypoxia/Reoxygenation Injury by Reducing Calcium Overload

Abstract: Intracellular Ca2+ mishandling is an underlying mechanism in hypoxia/reoxygenation (H/R) injury that results in mitochondrial dysfunction and cardiomyocytes death. These events are mediated by mitochondrial Ca2+ (mCa2+) overload that is facilitated by the mitochondrial calcium uniporter (MCU) channel. Along this line, we evaluated the effect of siRNA-targeting MCU in cardiomyocytes subjected to H/R injury. First, cardiomyocytes treated with siRNA demonstrated a reduction of MCU expression by 67%, which resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…and participates in I/R injury through the mechanism of MCU-Ca 2+ overload-mPTP opening. 8,19,20 In the present study, mito- 9 Previous studies have shown that calpain activation can cause cardiac dysfunction and apoptosis through a variety of signalling pathways. 23 In mitochondria, activated calpain cleaves and modifies apoptosis-inducing factor in mitochondria to release it from mitochondria to cytoplasm and initiate apoptosis.…”
Section: Several Studies Have Shown That Mcu Is Over-open During I/rmentioning
confidence: 67%
“…and participates in I/R injury through the mechanism of MCU-Ca 2+ overload-mPTP opening. 8,19,20 In the present study, mito- 9 Previous studies have shown that calpain activation can cause cardiac dysfunction and apoptosis through a variety of signalling pathways. 23 In mitochondria, activated calpain cleaves and modifies apoptosis-inducing factor in mitochondria to release it from mitochondria to cytoplasm and initiate apoptosis.…”
Section: Several Studies Have Shown That Mcu Is Over-open During I/rmentioning
confidence: 67%
“…Finally, it is of our concern the occupational exposure to NPs, especially those individuals with a cardiovascular disease. Recent work has shown that NP exposure exacerbates the cardiovascular damage, such as nanoSiO 2 induced alterations associated to contractile dysfunction [15,18] or pathophysiological conditions in which there is an increase of oxidative stress, such as myocardial ischemia or angina [39,48]. In this context, the tissue of patients will have higher susceptibility, which could trigger not only a lower dose cytotoxicity, but will likely provoke a nonconventional toxicity mechanism in specific scenarios of the disease, for example a patient with heart failure or cardiac hypertrophy [21].…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial membrane potential was measured by fluorometry using 5 μ M safranine [ 13 ]. Mitochondrial Ca 2+ uptake was determined with the metalochromic indicator, Arsenazo III, or calcium green 5N (5N-CG) [ 18 , 19 ], using a medium containing 50 μ M Arsenazo or 10 μ M 5N-CG, 10 mM succinate plus rotenone (0.1 μ g·ml −1 ), 200 μ M ADP, and 0.25 μ g oligomycin A. Pulses of 10 nmol Ca +2 were added every 3 minutes to reach a Ca +2 release due to MPT opening. Mitochondrial cytochrome c quantification from Cas-treated hearts was performed using Western blot analysis as described previously [ 11 ].…”
Section: Methodsmentioning
confidence: 99%